A TRANSIENT DRUG INDUCED LUPUS ERYTHEMATOSUS- LIKE ALLERGIC DRUG REACTION WITH MULTIPLE ANTIBODIES - Ana Maria Abreu Velez; Vickie M. Brown; Michael S. Howard (Our Dermatology Online, 2013)
Drug reactions may mimic several dermatoses, including lupus erythematosus. We present an 80 year old female patient on multiple medications, who presented with blisters on her hands and arms for two weeks, which then generalized to the rest of her body. The patient was evaluated by a dermatologist, and biopsies for hematoxylin and eosin (H&E) examination, as well as for direct immunofluorescence (DIF) and immunohistochemistry (IHC) were performed. The H&E biopsy examination revealed a mild, superficial, perivascular dermal infiltrate of lymphocytes, histiocytes and abundant eosinophils; neutrophils were rare. No vasculitis was noted. DIF revealed positive basement membrane (BMZ) staining, primarily with patchy Complement/C3c and fibrinogen; in addition, strong reactivity to dermal blood vessel was appreciated. Antibodies to cell junction-like structures were also noted in the epidermis and dermis with these two antibodies. IHC using similar immunoglobulins and complement components showed similar patterns. We observed that contrary to lupus erythematosus, neither IgG nor IgM were positive at the BMZ.